Microbial fuel cell treatment energy-offset for fertilizer production from human urine. (May 2022) - Sabin, Jeanne M.; Leverenz, Harold; Bischel, Heather N.
Abstract: Microbial fuel cells (MFCs) are a promising technology for simultaneous wastewater treatment and the biological conversion of organics to electrical energy. Yet effective MFC utilization of complex waste streams like human urine is limited by interference from high-strength organics (>5000 mg L −1 total organic carbon) and concentrated macronutrients (>500 mg L −1 nitrogen and phosphorus). This research assesses potential gains in MFC energy performance and organics treatment achieved by incorporating MFCs as a tertiary step in a human urine nutrient recovery system. The bioelectrochemical performance of benchtop-scale, low-cost MFCs was assessed using pre-treated human urine that was depleted in ammonium-nitrogen and phosphate (the "waste bottoms" of the urine nutrient recovery system). Performance of MFCs with waste bottoms as feedstock was compared to MFC performance with hydrolyzed real urine and synthetic urine as feedstocks. MFCs with waste bottoms produced 16.2 ± 14.8 mW mCat −2 (2.14 ± 1.95 W mCat −3 ), equivalent to 93% of the mean power density achieved by hydrolyzed urine after 32 days of operation. Coulombic efficiency over the full experimental runtime was 32.3 ± 4.1% higher for waste bottoms than urine. Waste bottoms helped avoid fouling of the ceramic membrane separator that occurs with urea hydrolysis and phosphate precipitation from urine. Enhanced ion separation was also observed, producing neutral pH in the anolyte and high pH (11.5) and electrical conductivity (25 dS m −1 ) in the catholyte. While several gains in performance were observed when using waste bottoms as feedstock, anolyte organics removal decreased 36.5% in MFCs with waste bottoms. This research indicates that pretreatment of source-separated urine via nutrient removal improves MFC electrical power generation and ion separation. Graphical abstract: Image 1 Highlights: Urine nutrient recovery effluent (waste bottoms) used for microbial fuel cells. Waste bottoms consisted of N- and P-depleted human urine. Waste bottoms achieved 32.3 ± 4.1% higher coulombic efficiency than untreated urine. Total organic carbon removal halved, while catholyte ion accumulation doubled. Supports pre-treatment process integration to improve urine feedstock performance.